Budidaya Tanaman Jagung Sebagai Bisnis Mandiri - Latif, Adi Sofyana; Arslan, Rijal; Ramdani, Chaeru Syahru; Septanta, Rananda (Jurnal PKM Manajemen Bisnis, 2025)
The purpose of this community service is to provide information on how to increase the potential of natural resources located in the Pondok Miri Pamulang area, which is an area that has quite high potential in the corn plant business in general, but currently it has not been utilized optimally by the surrounding community. Currently, most of the corn plants produced are sold individually without knowing the harvest that the accounting information system consumes. This is due to a lack of innovation from the local community. Therefore, corn cultivation is one way that can be done by harvesting quite small or large areas of land that can be put to good use, maintaining nutritional value and increasing economic value. With this cultivation empowerment, it is hoped that it can help improve the economy of the people of South Tangerang and take advantage of the harvest of Corn Plants for social welfare which is more durable and can give rise to various innovations in processing the Corn Plant itself in a sustainable manner.